Insights into the deselenization of selenocysteine into alanine and serine12. Issue 11 (19th August 2015) - Dery, Shahar; Reddy, Post Sai; Dery, Linoy; Mousa, Reem; Dardashti, Rebecca Notis; Metanis, Norman
Abstract : The deselenization of selenocysteine selectively removes the selenol group to give alanine under anaerobic conditions or serine under aerobic conditions (oxygen saturation). Abstract : The development of native chemical ligation coupled with desulfurization has allowed ligation at several new ligation junctions. However, desulfurization also converts all cysteine residues in the protein sequence into alanine. Deselenization of selenocysteine, in contrast, selectively removes the selenol group to give alanine in the presence of unprotected cysteines. In this study we shed more light onto the deselenization mechanism of selenocysteine to alanine and provide optimized conditions for the reaction. The deselenization can be accomplished in one minute under anaerobic conditions to give alanine. Under aerobic conditions (oxygen saturation), selenocysteine is converted into serine.